The digital economy and city innovation convergence – an empirical research based on the innovation value chain theory - Ding, Yijiu; Guo, Jianqiang; Ji, Yu; Guo, Kaiyi; Ma, Shenglin (Technological and Economic Development of Economy, 2025)
Within China’s strategy for innovation-driven development, digital economy (DE) plays a crucial role, significantly influences city innovation convergence. This study, grounded in the theoretical perspective of the innovation value chain theory (IVCT), divides innovation activities into two major phases: technological research phase and results transformation phase, and uses data from 283 Chinese cities spanning 2011 to 2021, it systematically explores, for the first time, the convergence characteristics of city innovation activities in each phase and delves deeply into the role of DE in this process. The findings reveal that city innovation in China’s cities demonstrates notable convergence characteristics during both technological research and achievements transformation phases. These convergence traits persist in both phases, even when accounting for spatial effects, particularly regarding the engagement of DE. Furthermore, in technological research phase, fiscal pressures faced by local governments diminish the effectiveness of DE in fostering city innovation convergence; but, during achievements transformation phase, such fiscal pressures do not impede DE’s capacity to enhance city innovation convergence. Lastly, the difference of city Innovation and entrepreneurial vitality during both technological research and achievements transformation phases restrict DE’s potential to support city innovation convergence, with a more pronounced diminishing effect observed in technological research phase. This study provides important decision-making support for policymakers and helps further uncover and unleash the potential of DE in promoting city innovation convergence. First published online 05 June 2025